2020
DOI: 10.1021/acs.analchem.0c01711
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Carbon and Nitrogen Isotopic Measurements of Heme B in Environmental Samples

Abstract: Heme B is an iron-coordinated tetrapyrrole molecule that acts as a cofactor in hemoproteins. It is expected to be ubiquitous in the environment, as b-type hemoproteins catalyze a variety of essential biochemical reactions. In this study, we developed an analytical method to quantify heme B in biological and environmental samples using high-performance liquid chromatography (HPLC) coupled to a photodiode array detector. The applicability of our method was further extended by the use of liquid chromatography/mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Specifically, a weak ion peak is located at m/z = 561.2, corresponding to PPIX. 44 In addition, a stronger ion peak is centered at m/z = 844.9, which is well assigned to molecular weight of PPIX with two [BMIm] + groups, owing to the PPIX containing double side-chain carboxyl groups.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Specifically, a weak ion peak is located at m/z = 561.2, corresponding to PPIX. 44 In addition, a stronger ion peak is centered at m/z = 844.9, which is well assigned to molecular weight of PPIX with two [BMIm] + groups, owing to the PPIX containing double side-chain carboxyl groups.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We found that bacteria in natural environments could adapt to lower heme concentrations than host‐associated bacteria, and bacteria in sediment required a higher hemin concentration than aquatic bacteria (Figure S7 and Table S7). The concentrations of total heme in sheep blood, sediment, and water were ~7 mM, 0.14–1.8 nmol/g, and 73.9–174.7 pM, respectively 30 . Bacteria in natural habitats have a low heme requirement, which may be an adaptation to oligotrophic environments.…”
Section: Resultsmentioning
confidence: 99%
“…162) A recent analysis of heme B, the most abundant heme species in the natural environment, suggested that the TDF of this compound may be relatively small. 163) The gap between the two approaches, amino acids and bulk, should narrow as more such data become available.…”
Section: Bulk Collagenmentioning
confidence: 99%